Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.